2021
DOI: 10.1101/2021.03.09.434442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of chronic JUUL aerosol inhalation on inflammatory states of the brain, lung, heart and colon in mice

Abstract: While health effects of conventional tobacco are well defined, data on vaping devices, including the most popular e-cigarette JUUL, are less established. Prior acute e-cigarette studies demonstrated inflammatory and cardiopulmonary physiology changes while chronic studies demonstrated extra-pulmonary effects, including neurotransmitter alterations in reward pathways. In this study we investigated effects of chronic flavored JUUL aerosol inhalation on inflammatory markers in brain, lung, heart, and colon. JUUL … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This blood plasma finding is interesting as another study in mice with 1 month of exposure to JUUL vape pods demonstrated increased TNF-α and IL-1β across subregions of the nucleus accumbens. 87 Nonetheless, human nicotine exposure via transdermal patch decreases the effects of LPS, increasing circulating concentrations of the antiinflammatory/regulatory cytokine IL-10. 88 Moreover, activation of the α7 nicotinic receptor blocks LPS-induced increases in TNF-α while not affecting IL-10, 14 suggesting that multiple nicotinic receptor subtypes play a role in this anti-inflammatory effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This blood plasma finding is interesting as another study in mice with 1 month of exposure to JUUL vape pods demonstrated increased TNF-α and IL-1β across subregions of the nucleus accumbens. 87 Nonetheless, human nicotine exposure via transdermal patch decreases the effects of LPS, increasing circulating concentrations of the antiinflammatory/regulatory cytokine IL-10. 88 Moreover, activation of the α7 nicotinic receptor blocks LPS-induced increases in TNF-α while not affecting IL-10, 14 suggesting that multiple nicotinic receptor subtypes play a role in this anti-inflammatory effect.…”
Section: ■ Introductionmentioning
confidence: 99%